2016
DOI: 10.1108/ijccsm-07-2014-0084
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic assessment of flooding among farm households in Anambra state, Nigeria

Abstract: Purpose – The purpose of this paper is to describe the extent of agricultural losses incurred by the farm households due to flood; to assess the farm households gender-based vulnerability to flood; to identify the coping strategies used by them; and to estimate factors that drive the choice of these coping strategies. Design/methodology/approach – Using both purposive and simple random sampling techniques, the paper selected 120 farm hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 5 publications
2
16
0
Order By: Relevance
“…Those women employed in the civil service who also took up farming activities fared much better. A similar finding was made by Enete et al [39] among farming households in Anambra state where men were more likely to be involved in other non-farm industries than women which helped them adapt better to recurrent floods. Domestic tasks which rural women mostly combine with farm work made it harder for them to engage in non-farm activities.…”
Section: Discussionsupporting
confidence: 81%
“…Those women employed in the civil service who also took up farming activities fared much better. A similar finding was made by Enete et al [39] among farming households in Anambra state where men were more likely to be involved in other non-farm industries than women which helped them adapt better to recurrent floods. Domestic tasks which rural women mostly combine with farm work made it harder for them to engage in non-farm activities.…”
Section: Discussionsupporting
confidence: 81%
“…Whilst some documents did not define the measures more precisely (e.g. Boamah et al 2015 ; Enete et al 2016 ; Evadzi et al 2018 ), others explicitly indicated them as providing labour, mental, financial, or material support, borrowing money, and food or shelter to affected family members or friends (e.g. Adelekan and Fregene 2015 ; Kielland 2016 ; Osman et al 2016 ; Frick-Trzebitzky 2017 ; Ajaero et al 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The impact of flooding on rice production in the Krueng Kluet Watershed, Aceh Province, Indonesia R S Pirngadi 1 and Rahmawaty 2,3* Utara, Medan, Indonesia. 2 Faculty of Forestry, Universitas Sumatera Utara, Medan, Indonesia. 3 Natural Resources and Environmental Management Study Program, Postgraduate School, Universitas Sumatera Utara, Medan, Indonesia IOP Publishing doi:10.1088/1755-1315/977/1/012113 2 crop failures which resulted in a decrease in rice production in the country [3].…”
Section: Introductionmentioning
confidence: 99%
“…From the data for the last three or four years, it is noted that almost every year 39,000 hectares of lowland rice land are flooded which results in a decrease in production yields and crop failure [1]. In the state of Anambra Nigeria, 100% of the number of lowland rice farmers who were used as research samples, 76.67% of them stated that 80% of their production was lost due to floods, while 18% of farmers lost their rice production due to flooding by 40-70% and the remaining 5% did not suffer losses due to flooding [2]. At the beginning of 2017, there were 27,754 ha of rice fields in Northeastern Bangladesh experiencing flash floods, as a result of which farmers experienced…”
mentioning
confidence: 99%